Pengaruh Metode Hypnobirthing Terhadap Tingkat Kecemasan Ibu Hamil Dalam Menghadapi Persalinan Di Wilayah Kerja Puskesmas Waimital - Zubaeda; Syahfitrah Umamity; Asih Dwi Astuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
Background: Pregnancy is a natural physiological process in a woman’s life, beginning with the fertilization of an ovum by a sperm cell and lasting approximately 37 to 40 weeks. As pregnancy enters its final stage, or the third trimester (between the 28th and 37th weeks), most pregnant women tend to experience anxiety. If not properly managed, anxiety may have adverse effects, both physically and psychologically, on the mother and the fetus. One of the interventions that can be applied to reduce anxiety levels in pregnant women is the hypnobirthing method. Objective: This study aims to analyze the effect of the hypnobirthing method on anxiety levels among third-trimester pregnant women in the working area of Waimital Community Health Center. Methods: This research employed a quasi-experimental design with a pre-test and post-test approach. The study sample consisted of 23 primigravida women in their third trimester, selected using a total sampling technique.. Results: The results of the bivariate analysis showed a decrease in anxiety levels after the hypnobirthing intervention, with a p-value of 0.000 < α = 0.05. Conclusion: The hypnobirthing method has a significant effect on reducing anxiety levels among third-trimester pregnant women in the working area of Waimital Community Health Center.